Pendampingan Pembuatan E-Book Interaktif Yang Keren Dan Kekinian Untuk Guru MTsN 3 Pekanbaru - Rika Melyanti; Anita Febriani (CV. Multi Kreasi Media, 2023)
Rapid technological developments have changed the educational landscape, requiring innovative teaching materials to enhance the learning experience. This community service focuses on providing assistance to subject teachers at MTsN 3 Pekanbaru School in creating engaging and cutting-edge interactive e-books. This activity uses a participatory approach, involving teachers in the design and co-development process. Through workshops and training sessions, teachers will gain skills in utilising multimedia elements, interactive features, and current pedagogical approaches to enrich e-book content. The expected outcome is a collection of modern and engaging e-books tailored to the specific needs and curriculum of MTsN 3 Pekanbaru, with the ultimate goal of improving the quality of learning media.